Recognition of handwritten Arabic (Indian) numerals using skeleton matching - Bassam Alqaralleh; Malek Zakarya Alksasbeh; Tamer Abukhalil; Harbi Almahafzah; Tawfiq Al Rawashdeh (Institute of Advanced Engineering and Science, 2020)
This paper brings into discussion the problem of recognizing Arabic numbers using a monocular camera as the only sensor. When a digital image is presented in this application, optical character recognition (OCR) can be exploited to comprehend numerical data. However, there has been a limited success when applied to the handwritten Arabic (Indian) numbers. This paper aims to overcome this limitation and introduces optical character recognition system based on skeleton matching. The proposed approach is used for handwritten Arabic numbers only. The experimental results indicate the effectiveness of the proposed optical character recognition system even for numbers written in worst case. The right system achieves a recognition rate of 99.3 %.